Prevention of Cryptosporidium and GIARDIA at the Human/Gorilla/Livestock Interface - Kalema-Zikusoka, Gladys; Rubanga, Stephen; Mutahunga, Birungi; Sadler, Ryan (Frontiers in Public Health, 2018)
Disease is one of the threats to critically endangered Mountain gorillas (Gorilla beringei beringei). A study implemented in 2010 investigated the prevalence of Cryptosporidium and Giardia, as part of a gorilla health-monitoring program through regular and abnormal fecal sample collection, and comparative pathogen analysis at the human/gorilla/livestock interface at Bwindi Impenetrable Forest. Samples collected from habituated and non-habituated gorillas, community-owned livestock herds, and people including symptomatic humans and staff working with gorillas were tested for Cryptosporidium and Giardia using the ImmunoSTAT Commercial Field Kit. Giardia was found in 3.2% of livestock, 40% of symptomatic humans from the local hospital and 8.1% of park staff, but not in gorillas. Cryptosporidium was found in 2% of habituated gorillas, 3.9% of livestock, and 58% of park staff. This is the first study of Cryptosporidium and Giardia through comparative analysis of fecal samples from humans, gorillas and livestock. Unlike previous studies in Bwindi, no Giardia was found in gorillas. The improving hygiene and sanitation of Bwindi local communities through Village Health and Conservation Teams (VHCTs) established in 2007, could have contributed to the decreased prevalence of Giardia in this mountain gorilla population. Cryptosporidium found in the gorillas could be associated with human interaction, similar to previous studies. Additional VHCTs were selected in two villages with positive human giardia samples and gorilla cryptosporidium samples. Local health centres were also informed to educate patients on health risks of unprotected water sources. We describe a One Health approach to addressing disease at the human/gorilla/livestock interface.